1969
DOI: 10.1203/00006450-196903000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in Protein Metabolism of Brain: I. Studies in Newborn Miniature Pigs at Varying Conceptual Ages

Abstract: ExtractT h e incorporation of L-phenylalanine-14C into protein of several brain areas and into liver of the miniature pig has been studied in viuo. A sequential decrease (approximately 50 %) in incorporation of labeled phenylalanine occurred during the first day of life in all brain regions ( fig. 1). There was no important difference in degree of incorporatn ioin the three brain regions examined. Labeling of liver protein was roughly threefold higher than in brain protein. A considerably smaller postnatal dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We have suggested that incorporation of tracers into the heterogeneous proteins of organ homogenates is best regarded as being analogous to the metabolic rate of whole organisms since it is a result of incorporation into numerous protein fractions existing in regional and subcellular locations [15]. A previous study of the labeling of subcellular fractions of brain proteins in vivo has revealed the highest rate of incorporation during 0.5-3 hr after injection to occur in the microso-ma1 protein fraction [5].…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested that incorporation of tracers into the heterogeneous proteins of organ homogenates is best regarded as being analogous to the metabolic rate of whole organisms since it is a result of incorporation into numerous protein fractions existing in regional and subcellular locations [15]. A previous study of the labeling of subcellular fractions of brain proteins in vivo has revealed the highest rate of incorporation during 0.5-3 hr after injection to occur in the microso-ma1 protein fraction [5].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of protein synthesis in fetal organs is generally higher than that seen in adult tissues [18,27]. As fetal organs mature functionally and structurally at differing rates, differences in their total nitrogen and protein content might be anticipated.…”
Section: Discussionmentioning
confidence: 99%